Physiological Response of Miscanthus x giganteus to Plant Growth Regulators in Nutritionally Poor Soil - Malinská, Hana; Pidlisnyuk, Valentina; Nebeská, Diana; Erol, Anna; Medžová, Andrea; Trögl, Josef (Plants (Basel, Switzerland), 2020)
Miscanthus x giganteus (Mxg) is a promising second-generation biofuel crop with high production of energetic biomass. Our aim was to determine the level of plant stress of Mxg grown in poor quality soils using non-invasive physiological parameters and to test whether the stress could be reduced by application of plant growth regulators (PGRs). Plant fitness was quantified by measuring of leaf fluorescence using 24 indexes to select the most suitable fluorescence indicators for quantification of this type of abiotic stress. Simultaneously, visible stress signs were observed on stems and leaves and differences in variants were revealed also by microscopy of leaf sections. Leaf fluorescence analysis, visual observation and changes of leaf anatomy revealed significant stress in all studied subjects compared to those cultivated in good quality soil. Besides commonly used Fv/Fm (potential photosynthetic efficiency) and P.I. (performance index), which showed very low sensitivity, we suggest other fluorescence parameters (like dissipation, DIo/RC) for revealing finer differences. We can conclude that measurement of leaf fluorescence is a suitable method for revealing stress affecting Mxg in poor soils. However, none of investigated parameters proved significant positive effect of PGRs on stress reduction. Therefore, direct improvement of soil quality by fertilization should be considered for stress reduction and improving the biomass quality in this type of soils.
Keywords: plant physiology; leaf fluorescence; plant stress; nutritionally poor post-military soil; Miscanthus x giganteus